Glucose production from oil palm trunk - Mohd Hafiz, Ab Majid @ Aziz (2011)
Oil palm trunk is one of the agricultural wastes which can be used as a raw material for production of glucose through fermentation process. It can be as another alternative way to reduce cost and also more environmental friendly. The main objective of this research is to produce glucose from oil palm trunk fibre using biological method. In biological method, the conversion of cellulose to glucose with the help of mix culture from oil palm sap. Twenty runs of experiment were carried out by using Design Expert Software based on three factors which are reaction time (0 – 24 hours), temperature (25°C - 40°C) and agitation speed (100 rpm – 300 rpm). Glucose was estimated by 3, 5dinitrosalicylic acid (DNS) method and the effect of three factors on glucose concentration employing oil palm trunk fibre were evaluated using Response Surface Methodology (RSM) two level, three-variable central composite rotatable design (CCRD). The optimum conditions derived via RSM were 10.41 hours of reaction time, temperature value of 30.45°C and agitation of 225.20 rpm. The result show that, the best condition to produce optimum glucose were achieved at 12.50 hours of reaction time, temperature value of 32.50°C and agitation speed of 300 rpm. There are also produce interaction between reaction time and temperature in order to produce glucose. After optimization, the glucose concentration was increased to 0.983454 mg/mL to give value of percentage of error which is 47.4%. As a conclusion, the objective of the research has been achieved. Glucose can be produced from oil palm trunk using biological method.